Analisis Postur Kerja Pada Bagian Packing Menggunakan Metode ManTRA Dan REBA - Rifka Alivia; Ferida Yuamita (CV. ALIM'SPUBLISHING, 2024)
PT. Indonesia Plafon Semesta is a company engaged in manufacturing, this company produces various kinds of PVC ceilings. Problems faced by PT. Indonesia Plafon Semesta is the activity of making PVC ceilings in the packing section, where the activity conditions or workers' posture is not good. When packing by squatting and bending, the position is less ergonomic, resulting in excessive force exertion and the risk of injury. This research aims to determine the level of complaints felt by workers in body parts by identifying them using the Nordic Body Map (NBM), Manual Task Risk Assessment (ManTRA) to determine the level of risk experienced by workers and knowing how many angles are formed. Rapid Entire Body Assessment (REBA) is used to calculate worker posture and provide a score of the worker's proposed posture using Anthropometry. Data processing was carried out using NBM calculations for workers who had the highest score of 51 and the lowest 44. Knowing the level of risk experienced by workers with Mantra protection with the back, forearms, neck and wrists > 15 and the angle formed in the REBA calculation using score 10. Improvement of the proposed posture with Anthropomerti with a TPO calculation of 32.5 cm and JTD cm of 69 by paying attention to the object being worked on with REBA calculation results having a score of 7.